Identifying Predictors of Hospital Readmission Following Congenital Heart Surgery through Analysis of a Multiinstitutional Administrative Database. (17th August 2014) - Smith, Andrew H.; Doyle, Thomas P.; Mettler, Bret A.; Bichell, David P.; Gay, James C.
Abstract Background Despite resource burdens associated with hospital readmission, there remains little multiinstitutional data available to identify children at risk for readmission following congenital heart surgery. Methods and Results Children undergoing congenital heart surgery and discharged home between January of 2011 and December 2012 were identified within the Pediatric Health Information System database, a multiinstitutional collection of clinical and administrative data. Patient discharges were assigned to derivation and validation cohorts for the purposes of predictive model design, with 17 871 discharges meeting inclusion criteria. Readmission within 30 days was noted following 956 (11%) of discharges within the derivation cohort (n = 9104), with a median time to readmission of 9 days (interquartile range [IQR] 5–18 days). Readmissions resulted in a rehospitalization length of stay of 4 days (IQR 2–8 days) and were associated with an intensive care unit (ICU) admission in 36% of cases. Independent perioperative predictors of readmission included Risk Adjustment in Congenital Heart Surgery score of 6 (odds ratio [OR] 2.6, 95% confidence interval [CI] 1.8–3.7, P < .001) and ICU length of stay of at least 7 days (OR 1.9 95% CI 1.6–2.2, P < .001). Demographic predictors included Hispanic ethnicity (OR 1.2, 95% CI 1.1–1.4, P = .014) and government payor status (OR 1.2, 95% CI 1.1–1.4, P = .007). Predictive model performance was modest among validation cohort (c statistic 0.68, 95% CI 0.66–0.69, P < .001). Conclusions Readmissions following congenital heart surgery are common and associated with significant resource consumption. While we describe independent predictors that may identify patients at risk for readmission prior to hospital discharge, there likely remains other unreported factors that may contribute to readmission following congenital heart surgery.